Effect of Leadership Style, Work Discipline, and Career Development on Employee Productivity of PT Yuri 8 Sejahtera - Herawati, Heny; Suldina, Farida; Lestari, Sri; Rafliansyah, Rafliansyah (Green Publisher Indonesia, 2025)
This study aims to obtain real evidence about the influence of